Launching the imagination : two-dimensional design - Stewart, Mary, 1952- (McGraw-Hill, 2002)
Two-dimensional design: elements; Color and composition; Two-dimensional design: organization; Cultivating creativity; Problem seeking and problem solving; Developing critical thinking...